KOMPOLAN JAILANIAN DALAM MENINGKATKAN NILAI-NILAI RELIGIUS PADA MASYARAKAT - Afifah, Muru’atul; Wasilah, Rodifatul; Hanun, Bisyarotul; Suhartatik, Idha (Universitas Al-Amien Prenduan, 2024)
AbstractMadurese society is still very thick with religious values, one of which is through kompolan which can be a forum in increasing religious values in society, especially in Pragaan Laok village, Pragaan District, Sumenep Regency. Kompolan jailanian which is a routine meeting every week in this village, is packed with readings of the book of manaqib sheikh Abdul Qadir jailani, religious tausiyah and arisan so that this village can sacrifice every year with an arisan system between members of the community. The focus of this research is how the implementation of kompolan jailanian in improving religious values in the community and its impact on the community of Pragaan Laok village. The research method used is Qualitative descriptive analysis with interview, observation, and documentation methods. The implementation of kompolan jailanian in improving religious values in the community is held every Friday night after isya', and the cultivation of religious values in three forms. Namely in the form of lectures, savings for qurban on Eid al-Adha and reading the book of manaqib Sheikh Abdul Qodir Jailani. And the implications of the existence of Kompolan jailanian for the community include: peace of mind, the desire to always get closer to Allah, a sense of kinship is increasingly intertwined, and the bond of friendship is maintained.